Dampak Peran Perempuan dalam Propaganda Terorisme - Asry nurma Ningsi (GHAITSA : Islamic Education Journal, 2025)
This abstract outlines the impact of women's roles in terrorist propaganda, which shows a significant transformation of their roles in acts of terrorism. In recent years, women's involvement in terrorist groups, especially those affiliated with ISIS, has increased, making them active actors in various acts of violence. This study identifies that women are often recruited through propaganda that utilizes social media, where they are exposed to narratives that are attractive and promise identity and spiritual goals. Through an analysis of the characteristics of radical groups and case examples, such as the involvement of women in the terrorist attacks in Surabaya, it can be seen that women play a role not only as supporters, but also as the main actors in acts of terror. This involvement is triggered by various factors, including social injustice, the search for identity, and the influence of a patriarchal environment that encourages them to seek equality through jihad. This study highlights the importance of understanding gender dynamics in the context of radicalization in order to formulate more effective prevention strategies against terrorism, as well as the need for women's active role in building family and community resilience against the influence of extremist ideology.